A Study on the Implementation of Jampersal Policy in Indonesia - Achadi, Endang L; Achadi, Anhari; Pambudi, Eko; Marzoeki, Puti (World Bank Group, Washington, DC, 2014)
Indonesia launched Jampersal in 2011, a nationwide program to accelerate the reduction of maternal and newborn deaths. The program was financed by central government revenues and provided free and comprehensive maternal and neonatal care with an emphasis on promoting institutional deliveries. Jampersal providers were public and enlisted private facilities at the primary and secondary levels. In 2013, the World Bank and the Center for Family Welfare, University of Indonesia conducted a qualitative and quantitative study to assess the implementation and impact of the program in Garut District and Depok Municipality in West Java Province. The study found that Jampersal utilization was highest among women who were least educated, poor, and resided in rural areas. Utilization was also high among women with delivery complications. The study showed Jampersal only had an impact where institutional delivery coverage was still low such as in Garut District. In this district, women were 2.4 times more likely to have institutional deliveries after Jampersal. The finding suggests implementation of Jampersal policy may have to be adjusted according to the utilization pattern for efficiency and effectiveness. The government discontinued Jampersal with the launching of the National Health Insurance Program (JKN) on January 1, 2014. The study s findings indicate the merit in reevaluating the policy to terminate the program, given that Jampersal helped increase institutional deliveries while voluntary participation in JKN remains low.